Statistical Analysis of Tribology Friction Data in a Long Repeated Sliding System - Qurbonov O., Axralov H , Kanao Fukuda, Muminov Z. (International Journal of Advanced Science and Technology, 2020)
In this paper, statistical methods were used to conjecture friction and wear mechanisms for quantitative tribology data obtained by pin-on-disk apparatus in the long stage of sliding. The slopes of data are investigated for several cumulative and probability distribution functions and it is shown that stable distribution is most suited for modelling data distributions, more prone to outliers than the normal distribution. Stability parameter, skewness parameter, scale parameter and location parameter of the stable distribution for different sliding rotations were compared.